STRATEGI PENGUATAN ETIKA DAN INTEGRITAS BIROKRASI DALAM RANGKA PENCEGAHAN KORUPSI GUNA MENINGKATKAN KUALITAS PELAYANAN - Hj. Sedarmayanti Hj. Sedarmayanti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Bureucracy ethics and integrity become the public issue recently. This article copes to analyze reflectively about ethics and bureaucracy integrity problems with various perspective. Recognition, understanding, and implementation of the ethics infrastructure in bureaucratic life, become an important part of the effort of prevention corruption in order to enhance service quality. The availability of guideline, handling system and apparatus management correctly also becomes one of the ethics and bureaucracy integrity reinforcement strategies. Those things are not separated from the purpose of bureaucratic reform that government claimed.